ARE CHILDREN SMARTER (OR MORE SO ARE CHILDREN SMARTER (OR MORE SOCIALIZED) BECAUSE OF THE INTERNET? ARE CHILDREN SMARTER (OR MORE SOCIALIZED) BECAUSE OF THE INTERNET? - Арчабаева, Наргиза (Maktabgacha taʼlim jurnali, 2022)
The article discusses whether today’s children smarter or more social as a result of their access to the entire world . That will be the subject of this article through today's generation and their technological understanding. Today's youngsters are neither brighter nor more social because of the Internet.